Diversidade e estruturação genética de Brachyteles hypoxanthus (Primates: Atelidae) em um ambiente fragmentado no município de Santa Maria de Jetibá (ES) usando DNA mitocondrial e nuclear - Alvarenga, Clara Scarpati (2010)
Brachyteles hypoxanthus, northern muriqui, is threatened by the small number of individuals in the wild, distributed in only 12 isolated populations, being classified as "critically endangered" species. Mitochondrial DNA (mtDNA) studies revealed the population of Santa Maria de Jetibá (SMJ) as a Management Unit, despite of habitat smaller and highly fragmented. Our objective was to assess whether the populations of each fragment also form different units. We analyzed 43 individuals from six areas of the municipality using five microsatellite loci and 366 bp of hypervariable region I (D-loop, mtDNA). Moderate levels of genetic diversity (Dg=0,74) and heterozygosity (Hobs=0,60) were found with nDNA. Populations São Sebastião de Belém (SSB) and Córrego do Ouro 1 (CO1) deviated from HWE and were significants in the inbreeding coefficient (Fis=0,259 and 0,206; respectively). Were detected seven haplotypes (mtDNA), with moderate haplotype diversity (h=0,7540). The H1 haplotype was unique to SSB, while the other three populations shared haplotypes (H2, H3 and H5). Not were discarded the hypothesis of population stability. There was a weak genetic structure for nDNA (Fst=0,0768), but strong structure for mtDNA (Fst=0,58013), with SSB distinct from other populations (0,65256=Fst=0,94310). Moderate genetic diversity in SMJ unexpected for a species critically endangered and is probably due to the long generations, since the populations had weak genetic structure between themselves (nDNA). However, deviations from HWE and the predominance of one haplotype of mtDNA for SSB may be signs of the effects of genetic drift, since it does not rule out the hypothesis of demography equilibration. These effects are consistent with the proposal that genetic drift tends to be more intense in island populations, an analogy to forest fragments of SMJ. Seen the low differentiation in allele frequencies and sharing of haplotypes, our data suggest that the population of SMJ in particular should not be treated as different units. Based on this, the genetic diversity simulations show that the increased connectivity of forest fragments in SMJ over the medium and long term can be an essential step in the restoration, maintenance and conservation of northern muriqui in the municipality